2017
DOI: 10.1007/s10461-017-1980-6
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Physical and Mental Well-Being in Adults with and Without HIV

Abstract: Resilience has been related to improved physical and mental health, and is thought to improve with age. No studies have explored the relationship between resilience, ageing with HIV, and well-being. A cross sectional observational study performed on UK HIV positive (N = 195) and HIV negative adults (N = 130). Associations of both age and ‘time diagnosed with HIV’ with resilience (RS-14) were assessed, and the association of resilience with depression, anxiety symptoms (PHQ-9 and GAD-7), and problems with activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 37 publications
(70 reference statements)
4
60
1
4
Order By: Relevance
“…While prior research has reported social support as a variable important to fostering resilience (e.g., Bhat et al, 2015;Earnshaw et al, 2015), to our knowledge this study is unique in contributing to the resilience literature regarding the importance of a gender-based approach to tailoring health services for WLWH. Corroborating prior research (Farber et al, 2000;Fumaz et al, 2015;McGowan et al, 2018), we found that resilience was associated with improved physical and mental HR-QoL among WLWH. We found that economic insecurity did play a role in this relationship, whereby lower resilience was associated with increased economic insecurity, which in turn was associated with lower levels of mental and physical HR-QoL.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While prior research has reported social support as a variable important to fostering resilience (e.g., Bhat et al, 2015;Earnshaw et al, 2015), to our knowledge this study is unique in contributing to the resilience literature regarding the importance of a gender-based approach to tailoring health services for WLWH. Corroborating prior research (Farber et al, 2000;Fumaz et al, 2015;McGowan et al, 2018), we found that resilience was associated with improved physical and mental HR-QoL among WLWH. We found that economic insecurity did play a role in this relationship, whereby lower resilience was associated with increased economic insecurity, which in turn was associated with lower levels of mental and physical HR-QoL.…”
Section: Discussionsupporting
confidence: 77%
“…A rich body of literature has established that resilience is associated with positive health benefits among persons living with HIV (PLWH), including viral suppression (Dale et al, 2014), treatment adherence (Dale et al, 2014), and physical and mental health dimensions of health-related quality of life (HR-QoL) (Farber, Schwartz, Schaper, Moonen, & McDaniel, 2000;Fumaz et al, 2015;McGowan et al, 2018). Less studies with PLWH have explored social ecological pathways to resilience and its association with HR-QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results indicated that they felt more optimistic about this situation. This is important because resilience has been linked to positive emotions in stressful situations, 16 overall well-being, 42 life satisfaction, 43 self-rated health 44 and better quality of life (physical and psychological) in older adults. 17 The importance of promoting resilience in the medical staff during the COVID-19 pandemic has been highlighted, 10 but also the general population should be resilient during these tough days.…”
Section: Discussionmentioning
confidence: 99%
“…resilience, grit, and self-rated successful aging (SRSA) among PLWH. Two studies have found an association between higher resilience and lower depressive symptoms among PLWH (Dale et al, 2015;McGowan et al, 2018). Similarly, in PLWH greater grit (i.e., the perseverance and passion for long term goals; (Duckworth et al, 2007)) has been negatively associated with major depression (Moore et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%